18F-FDG PET/CT Plays a Limited Role in Replacing Bone Marrow Biopsy for Newly Diagnosed Advanced-Stage Patients With Extranodal Natural Killer/T-Cell Lymphoma - Yang, Chunli; Wu, Wanchun; Zhou, Huijie; Zhao, Sha; Tian, Rong; Xiang, Maya; Zou, Liqun (Frontiers in Oncology, 2022)
Purpose The role of 18F-2-fluoro-2-deoxy-D-glucose positron emission tomography/computed tomography (18F-FDG PET/CT) in evaluating bone marrow (BM) involvement (BMI) among patients with extranodal natural killer/T-cell lymphoma (ENKTL) is poorly understood. This study investigated whether PET/CT could replace bone marrow biopsy (BMB) in treatment-naive ENKTL patients. Methods Newly diagnosed ENKTL patients (n=356) who received BMB and PET/CT to evaluate BMI at time of diagnosis were retrospectively reviewed in West China Hospital between August 2008 and January 2020. BMI diagnosis was confirmed using BM histology. Clinical characteristics, survival outcomes, and prognostic indicators were summarized and analyzed. Results The cohort included 356 cases, of whom 261 were diagnosed with early-stage and 95 with advanced-stage ENKTL by PET/CT before initial treatment. No early-stage patients were identified with BMI by either BMB or PET/CT. Among the advanced-stage patients, 26 were BMB positive, and 12 of 22 patients (54.5%) with positive PET/BM results were also BMB positive. The sensitivity and specificity of PET/CT to detect BMI were 46% and 97%, respectively. The progression-free survival (PFS) and overall survival (OS) of PET/BM negative patients were markedly longer (p=0.010 and p=0.001 for PFS and OS, respectively), which was consistent with results of the BMB (p=0.000 for both PFS and OS). Conclusions Although 18F-FDG PET/CT has the potential to replace BMB in the initial staging of early-stage ENKTL patients, baseline PET/CT could not provide an accurate BMI evaluation for advanced-stage patients. A prospective study is required to confirm the diagnostic performance of BMI identification by PET/CT, along with targeted BMB and MRI for advanced-stage patients.